Are dementia services and support organisations meeting the needs of Lesbian, Gay, Bisexual and Transgender (LGBT) caregivers of LGBT people living with dementia? A scoping review of the literature. (3rd October 2022) - Di Lorito, Claudio; Bosco, Alessandro; Peel, Elizabeth; Hinchliff, Sharron; Dening, Tom; Calasanti, Toni; de Vries, Brian; Cutler, Neil; Fredriksen-Goldsen, Karen I.; Harwood, Rowan H.
Abstract: Objectives: More than 60% of people with dementia live at home, where assistance is usually provided by informal caregivers. Research on the experiences of the Lesbian, Gay, Bisexual and Transgender (LGBT) caregivers is limited. This scoping review of the literature synthesizes international evidence on support provision for the population of LGBT caregivers. Methods: Eight electronic databases and Google Scholar were searched using terms including 'Dementia', 'LGBT' and 'Caregiver' for all types of articles, including empirical studies, grey literature and sources from charity/third sector/lobbying organisations. Article selection was performed by two raters. Data were analysed through deductive thematic analysis, and three themes were established a priori: Distinct experiences of LGBT caregivers; current barriers to support; strategies to overcome the current challenges. Results: Twenty articles were included. Distinct experiences of LGBT caregivers included a loss of LGBT identity, the impact of historical events, families of choice, and disclosing LGBT identities. Current barriers to support included poor representation of LGBT caregivers in support services, negative attitudes of staff and reluctance of caregivers to seek support. Strategies to overcome the current challenges included staff awareness training and kite-marking inclusion. Conclusion: Limited cultural competency of staff and a subsequent reluctance to seek help have an impact on use of support services among LGBT caregivers. Implications for practice include the development of cost-effective, feasible, and acceptable inclusiveness training for services. Implications for policy include implementation in organisations of top-down agendas supporting staff to understand sexuality and non-heteronormative relationships in older age.